2014
DOI: 10.1111/saje.12050
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Inefficient Expenditure in Local Government: A Free Disposable Hull Analysis of a Sample of South African Municipalities

Abstract: Municipalities in South Africa play a pivotal role in the provision of basic services to communities. However, local government as a sphere in the country is notorious for its spending inefficiency, which is cited as a major factor in service delivery failure. This paper quantifies inefficient expenditure at the local government level by estimating efficiency scores for a sample of 129 municipalities in South Africa from the 2005/2006 to the 2009/2010 municipal financial years. In essence, this paper examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…These results indicate a superior performance of municipalities than the results of Mahabir (2014), in which all services of the municipalities were assessed using FDH. Mahabir (2014) found that an average efficiency of approximately 45% can be expected for municipalities over the years assessed. The results of the current study indicate a higher efficiency; however, this study considers water services provision of municipalities only and uses a DEA technique.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These results indicate a superior performance of municipalities than the results of Mahabir (2014), in which all services of the municipalities were assessed using FDH. Mahabir (2014) found that an average efficiency of approximately 45% can be expected for municipalities over the years assessed. The results of the current study indicate a higher efficiency; however, this study considers water services provision of municipalities only and uses a DEA technique.…”
Section: Resultsmentioning
confidence: 92%
“…The input used in the research was operating expenditure per capita and the outputs used were the number of consumer units receiving access to piped water, grid electricity, toilet facilities and refuse removal. Mahabir (2014) found that the average efficiencies achieved by the municipalities varied between 42% and 46% over the years assessed. The results indicated that the municipalities considered in this study could utilise 54 to 58% less expenditure to achieve their current output levels.…”
Section: Dea In Water Service Provisionmentioning
confidence: 98%
“…Interestingly, despite the different methods and data used, results for the efficiency levels in U.S. local governments are quite consistent, varying between 0.81 and 0.84. Three studies assessed provision of basic services in local municipalities in South Africa from 2005 to 2010 (Dollery and van der Westhuizen, ; Mahabir, ; Monkam, ). In general, they show low efficiency levels, scoring from 0.17 to 0.64.…”
Section: Country‐level Analysismentioning
confidence: 99%
“…(), Kutlar and Bakirci (), Nakazawa (, ), Ashworth et al. (), Pevcin (, ), Mahabir (), Yusfany (), Andrews and Entwistle ().…”
unclassified
See 1 more Smart Citation